2016
DOI: 10.1016/j.ensci.2016.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Hospital-based study on emergency admission of patients with Parkinson's disease

Abstract: ObjectiveParkinson's disease (PD) is a progressive neurodegenerative disease. As the severity of disease worsens, patients have lower tolerance for treatments and occasionally need to be hospitalized. This study focuses on characteristics of patients with PD who were emergently admitted to our hospital and evaluates their prognosis during hospitalization.MethodsHospital-based study on emergency admission was conducted in a consecutive series of patients with PD between April 2009 and March 2015.ResultsA total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 13 publications
2
14
0
3
Order By: Relevance
“…Infections, mainly UTI and pneumonia were the topmost reason for admission among people with PD. This supports data provided by a number of other studies which identified infectious diseases including aspiration pneumonia, UTI and others as common reasons for emergency admissions [14,31,45,48]. In contrast, falls/fractures are the most reported in other studies.…”
Section: Discussionsupporting
confidence: 89%
“…Infections, mainly UTI and pneumonia were the topmost reason for admission among people with PD. This supports data provided by a number of other studies which identified infectious diseases including aspiration pneumonia, UTI and others as common reasons for emergency admissions [14,31,45,48]. In contrast, falls/fractures are the most reported in other studies.…”
Section: Discussionsupporting
confidence: 89%
“…Deteriorated sensitivity and intensity of cough reflex also influence the risk of aspiration pneumonia (63). Aspiration pneumonia was the most common reason for the emergency admission of patients with PD whose disease duration was >5 years (64). Most of them exhibited abnormalities on their VFSS, cognitive impairment, and a history of psychiatric symptoms.…”
Section: Progression and Management Of Dysphagia In Pdmentioning
confidence: 99%
“…PHS is reported in the context of non-compliance with dopaminergic medications, during severe “off” periods, concurrent illness, dysphagia or changes in diet, and withholding of medications prior to medical or surgical procedures [ 30 , 31 ]. For example, PHS may be observed after surgery in patients with PD instructed to stop dopamine medications prior to surgery and not restarted promptly post-operatively.…”
Section: Hyperthermic Syndromesmentioning
confidence: 99%